2007
DOI: 10.1002/14651858.cd004659.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet agents for preventing pre-eclampsia and its complications

Abstract: Antiplatelet agents, largely low-dose aspirin, have moderate benefits when used for prevention of pre-eclampsia and its consequences. Further information is required to assess which women are most likely to benefit, when treatment is best started, and at what dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
377
4
49

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 549 publications
(447 citation statements)
references
References 134 publications
10
377
4
49
Order By: Relevance
“…Low-dose aspirin and heparin have been used to improve placental function and decrease stillbirth, but a high number needed to treat with aspirin and uncertain efficacy has prevented widespread adoption of these interventions. 74 Although evidence is incomplete, preconception care is a potentially valuable intervention in stillbirth prevention, yet only 28% of care providers said that preconception care for women with risk factors was implemented mostly or always in their facilities.…”
Section: Quality Of Care Uptake Of Interventions In Stillbirth Prevenmentioning
confidence: 99%
“…Low-dose aspirin and heparin have been used to improve placental function and decrease stillbirth, but a high number needed to treat with aspirin and uncertain efficacy has prevented widespread adoption of these interventions. 74 Although evidence is incomplete, preconception care is a potentially valuable intervention in stillbirth prevention, yet only 28% of care providers said that preconception care for women with risk factors was implemented mostly or always in their facilities.…”
Section: Quality Of Care Uptake Of Interventions In Stillbirth Prevenmentioning
confidence: 99%
“…While there is currently no effective preventative measure, a recent meta-analysis has suggested that low-dose aspirin may reduce the incidence of pre-eclampsia by 10%. 44,45 Early identification of women at risk of pre-eclampsia facilitates targeted surveillance and intervention. 46,47 There are likely to be significant advantages in predicting preeclampsia in the first, as opposed to the second trimester; given that the disease process (failure of adequate trophoblastic invasion) is already established by the mid-second trimester, it seems likely that any successful preventative measure will need to be instituted as early in pregnancy as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Descreve-se redução do risco de 17% no desenvolvimento de pré-eclampsia com o uso de agentes antiplaquetários 3 . Neste estudo, foi detectada redução significativa no desenvolvimento de pré-eclâmpsia grave após intervenção com enoxaparina, como se observa na Tabela 1.…”
Section: Discussionunclassified
“…Os agentes antiplaquetários também estão associados à redução no risco relativo (RR) de 8% no parto pré-termo, redução do RR de 14% para óbitos fetais/ perinatais e RR de 10% em recém-nascidos com baixo peso ao nascimento 3 . Esses resultados vêm ao encontro dos apresentados nesta pesquisa, uma vez que se observa redução significativa no número de abortos e óbitos fetais/ perinatais após instituição das estratégias de diagnóstico e intervenção para as trombofilias.…”
Section: Discussionunclassified
See 1 more Smart Citation